The Effect of Microgravity on Central Aortic Blood Pressure. (25th July 2018) - Seibert, Felix S; Bernhard, Fabian; Stervbo, Ulrik; Vairavanathan, Sinthuya; Bauer, Frederic; Rohn, Benjamin; Pagonas, Nikolaos; Babel, Nina; Jankowski, Joachim; Westhoff, Timm H
Abstract: BACKGROUND: Blood pressure has been traditionally measured at peripheral arteries. In the past decade, evidence has grown that central aortic blood pressure may be a more powerful predictor for cardiovascular events, but data on its regulation are rare. The present work examines the impact of microgravity on central blood pressure for the first time. METHODS: We performed 7 parabolic flights with 22 seconds of weightlessness in each parabola. Hemodynamic parameters including central systolic blood pressure were measured noninvasively in a free-floating position in 20 healthy subjects (19–43 years of age). RESULTS: Arterial elasticity at rest was normal in all participants (augmentation index 14% (interquartile range (IQR) 10–22), pulse wave velocity 5.2 m/s (IQR 5.0–5.4)). Transition of 1g to 0g led to a significant increase of central systolic blood pressure from 124 (IQR 118–133) to 127 (IQR 119–133) mm Hg ( P = 0.017). Cardiac index augmented significantly from 2.5 (IQR 2.2–2.8) to 2.7 (IQR 2.3–3.0) l/min/m 2 ( P < 0.001), while peripheral vascular resistance showed a decrease from 1.30 (IQR 1.14–1.48) to 1.25 (IQR 1.15–1.40) s × mm Hg/ml ( P = 0.037). Peripheral systolic blood pressure did not change significantly ( P > 0.05). CONCLUSION: Whereas there is a multitude of studies on the effects of microgravity on peripheral blood pressure, this study provides first data on central aortic blood pressure. An acute loss of gravity leads to a central blood volume shift with an augmentation of cardiac output. In healthy subjects with normal arterial stiffness, the compensatory decrease of peripheral resistance does not outweigh this effect resulting in an increase of central blood pressure.